Amnesiac (AMN) gene and cnc/Nrf2-redox responses in fruit fly model of memory impairment co-administered Solanum leaves and donepezil - Odunayo M. Agunloye; Opeyemi B. Ogunsuyi; Odunayo O. Oluokun; Ganiyu Oboh (Elsevier, 2024)
Background: Considering that Alzheimer disease (AD) is a disease of multiple etiological theories, there is a continuous quest for multitarget approach for its management. In view of this, combinatory approach using therapeutic drugs and functional foods is gaining wide popularity. Leaves of Solanum spp such as S. nigrum and S. macrocarpon which are cultivated across the world including Southeast Asia and Africa has several health-promoting benefits. While we have previously reported that both S. nigrum and its relative of African origin S. macrocarpon has neuroprotective properties, however, there is dearth of information on their possible interaction with anti-amnesic drugs which suggests a possible novel therapeutic hypothesis. Purpose: This study investigated the effects of combining Black Nightshade (BN; S. nigrum) and African eggplant (AE; S. macrocarpon) dietary inclusions with donepezil, to gain insights into the molecular mechanisms underlying any synergistic effects resulting from the interaction between these food components and the drug, with the ultimate goal of developing comprehensive intervention. Methods: Six to eight-day-old flies were grouped into five. The treatment lasted for seven days and the survival rate of the flies was recorded. Thereafter, acetylcholinesterase (AChE) activity and antioxidant status of the head tissue were assayed. Also, the level of expression of amnesiac gene (AMN) and nuclear factor erythroid 2-related factor 2 (Nrf2) gene, as well as phytochemical present in the samples were quantified. Results: The phytochemical screening results revealed abundance of quercetin and kaempferol. Furthermore, the induced group exhibited impaired cholinergic system, increased mortality rate and oxidative stress, as well as reduced catalase activity compared to the control. Treatment with donepezil and the combinations improved flies survival rate and ameliorated the impaired cholinergic system and oxidative stress levels. Similarly, the downregulated expression of AMN and cnc/Nrf2 genes observed in the induced flies was upregulated in the treated groups. The HPLC result revealed the abundance of quercetin in both samples, which could be attributed to their neuroprotective and antioxidant properties. Conclusions: The administration of donepezil with the consumption of AE but not the combination of donepezil with BN, significantly improved the memory impairment through interactions with the AMN and cnc/Nrf2 genes but not AChE activity.